A novel "video‐game" simulator for training fetoscopic laser coagulation of anastomoses in twin‐to‐twin transfusion syndrome. (11th March 2021) - Windrim, Rory; Young, Alexander; LeBouthillier, Francis; Ryan, Greg; Van Mieghem, Tim; Abbasi, Nimrah; Keunen, Johannes; D'Souza, Rohan; Kfouri, Julia
Key Points/Highlights:  : We have developed a high‐fidelity interactive "video‐game" simulator in order to teach fetoscopic laser ablation of placental anastomoses for twin‐twin transfusion syndrome This simulator may be used by teachers in order to provide metrics‐based simulator education to multiple trainees, in both hands‐on and distanced learning settings What is already known about this topic?: The use of simulation improves training of the fetoscopic laser techniques utilized in the treatment of twin‐twin transfusion syndrome A number of mannequins have been developed to aid this education What does this study add?: Two new simulators are described for twin‐twin transfusion syndrome training—silicone and digital The digital simulator is a novel digital video game virtual format This new format has enhanced interactivity and has the potential to enable distance learning